Modelling and Numerical Valuation of Power Derivatives in Energy Markets (Advances in Applied Mathematics and Mechanics, 2012)
In this work we investigate the pricing of swing options in a modelwhere the underlying asset follows a jump diffusion process. We focus on thederivation of the partial integro-differential equation (PIDE) which will be appliedto swing contracts and construct a novel pay-off function from a tree-based pay-offmatrix that can be used as initial condition in the PIDE formulation. For valuingswing type derivatives we develop a theta implicit-explicit finite difference schemeto discretize the PIDE using a Gaussian quadrature method for the integral part.Based on known results for the classical theta-method the existence and uniquenessof solution to the new implicit-explicit finite difference method is proven. Variousnumerical examples illustrate the usability of the proposed method and allow usto analyse the sensitivity of swing options with respect to model parameters. Inparticular, the effects of number of exercise rights, jump intensities and dividendyields will be investigated in depth.